Kajian Bahan Organik Dasar Perairan di Rawa Kongsi Kecamatan Patumbak Kabupaten Deli Serdang Provinsi Sumatera Utara (Study of Bottom Waters Organic Materials at Kongsi Swamp Patumbak District of Deli Serdang Regency, North Sumatra) - Ratna Dewi Sinaga; Hesti Wahyuningsih; rusdi leidonald (AQUACOASTMARINE, 2016)
Organic materials are one of the environment fertility indicator both on land and sea. Ground’s organic matter content reflected the soil and waters quality to be a factor in an environment of waters quality. Kongsi swamp is an inundated inland waters which is used for fishing, farming, agricultural, and household waste disposal that impacted surroundings environment. This study aimed to assess the organic matter content and its relationship with the availability of nitrogen and phosphorus nutrients in Kongsi swamp. The study took place in February – April 2016. The method used to determine the location was purposive sampling which were divided into four stasions based on different activities. Analysis was conducted on substrate with three segments based on different depth include C organic, total nitrogen, total phosphorus, soil texture and pH, physical – chemical water analysis.The result showed that Kongsi swamp waters was in medium category with a total of nitrogen range from 0,05 to 0,56%, highest C organic was 3,9% and highest phosphorus was 27 ppm at the third stasion showed high organic matter content with a lot of Eceng Gondok. Using Pearson correlation analysis, accumulation of organic materials on the bottom waters sediment had a stronger relationship with the nitrogen availability which was very strong compared to the phosphorus availibility in each segment.Keywords : Kongsi Swamp, Organic Material, Nitrogen, Phosphorus Pearson Correlation Analysis